Pengaruh Latihan Split Squat Jump dan Lunges terhadap Kekuatan Otot Tungkai Kenshi Shorinji Kempo Buleleng - Bayu Suprastya; Luh Putu Tuti Ariani; Anak Agung Ngurah Putra Laksana (MAN Insan Cendekia Jambi, 2026)
This research attempts to evaluate the efficacy of Split Squat Jump and Lunges Bodyweight Training on improving the leg muscle strength of Shorinji Kempo kenshi in Buleleng Regency. The study employed a pretest-posttest two-group design and a quasi-experimental methodology. The participants were 30 kenshi (aged 15-18 years), divided into two groups using the Matched Subject Ordinal Pairing (MSOP) method. Measurements were taken using a Leg Dynamometer. The training program lasted for 8 weeks with a frequency of 3 times per week. Data were analyzed using paired t-tests and independent t-tests at a significance level of 0.05. The results showed significant improvements in both groups; the split squat jump group increased by an average of 5.4 kg (Sig. 0.001) and the lunges group increased by 5.6 kg (Sig. 0.001). The independent t-test yielded a Sig. value of 0.937, indicating no significant difference in effectiveness between the two exercises. It was concluded that both training methods are equally effective in increasing the leg muscle strength of Shorinji Kempo kenshi.